STRUCTURE OF IMPERFECT VECTORS FOR THE ADDED WHOLE CURVES - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is shown, that the structure of imperfect vectors for the added whole curve of scinchennogo order is some other, than for the ordinary whole curve of endding order.